2008
DOI: 10.1080/03008200802148652
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Binding Protein Pleiotrophin: An Important player in the Angiogenic Process

Abstract: Angiogenesis, the formation of new blood vessels from pre-existing ones, is a fundamental process in life, being also significantly important in several pathological situations. Pleiotrophin is a heparin-binding growth factor with pleiotrophic actions and significant role(s) in the formation of new blood vessels, being regulated by angiogenic stimuli and acting directly on endothelial cells. In this minireview, we summarize data on the regulation and mode of action of pleiotrophin and its involvement in physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Pleiotrophin (PTN), also known as heparin affin regulatory peptide or heparin binding growth-associated molecule, is a secreted growth factor that together with midkine (MK) forms a family of structurally related heparin binding growth factors that share many biological activities, the best characterized being neural development and tumor growth. Besides a direct effect of PTN on tumor cells, there is a plethora of reports indicating a positive correlation between PTN and in vivo or in vitro angiogenesis (1,2). The receptors of PTN involved in its angiogenic effects are, however, still unidentified.…”
mentioning
confidence: 99%
“…Pleiotrophin (PTN), also known as heparin affin regulatory peptide or heparin binding growth-associated molecule, is a secreted growth factor that together with midkine (MK) forms a family of structurally related heparin binding growth factors that share many biological activities, the best characterized being neural development and tumor growth. Besides a direct effect of PTN on tumor cells, there is a plethora of reports indicating a positive correlation between PTN and in vivo or in vitro angiogenesis (1,2). The receptors of PTN involved in its angiogenic effects are, however, still unidentified.…”
mentioning
confidence: 99%
“…Clinical studies have shown that the release of HBP in many bacterial diseases is considered an important marker of severe infection, especially sepsis [ 6 , 7 ]. Neutrophils play a major role in a variety of cells involved in airway inflammation in COPD, and blood heparin-binding protein is a protein with bactericidal and chemotactic effects released when neutrophils are stimulated [ 8 , 9 ]. However, the current research on the relationship between blood HBP and COPD is very rare in China and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2011 (He et al, 2010). Η ορδθή έηθναζδ ηδξ moesin ιπμνεί κα πνδζζιμπμζδεεί ηαζ ςξ πνμβκςζηζηυξ δείηηδξ ημο πθαηχδμοξ ηανηζκχιαημξ ημο ζηυιαημξ (Mikelis et al, 2007;Mikelis and Papadimitriou, 2008;Papadimitriou et al, 2009;Pantazaka and Papadimitriou, 2012). Οζ αββεζμβεκεηζηέξ δνάζεζξ ηδξ ΡΣΝ, ηαζ εζδζηά υζεξ αθμνμφκ ζηδ ιεηακάζηεοζδ ηςκ εκδμεδθζαηχκ ηοηηάνςκ, θαίκεηαζ κα δζαιεζμθααμφκηαζ απυ ημκ οπμδμπέα ηδξ ιε δνάζδ θςζθαηάζδξ ηονμζίκδξ α/γ (RPTPα/γ) (Polykratis et al, 2005) ηαζ ηδκ ζκηεβηνίκδ α κ α 3 (Mikelis et al, 2009).…”
Section: ο ξφινο ηεο Moesin ζηνλ θαξθίλνunclassified